Population dynamics of the freshwater crab Dilocarcinus pagei in tropical waters in southeastern Brazil - Davanso, Thiago Maia [UNESP]; Taddei, Fabiano Gazzi; Simões, Sabrina Morilhas [UNESP]; Fransozo, Adilson [UNESP]; Costa, Rogério Caetano da [UNESP] (Oxford University Press (OUP), 2013)
In the northwestern region of the state of São Paulo, Brazil, the freshwater crab Dilocarcinus pagei Stimpson, 1861 is usually sold as bait for several fish species for sport fishing. Thus, knowledge of the reproductive biology of this species is essential to provide information for maintaining natural stocks and implementing future farming initiatives. The objective of this study was to investigate the population dynamics of the red freshwater crab D. pagei, focusing on reproductive and juvenile recruitment periods, sex ratio, and individual growth. Sampling was performed monthly from October 2005 to September 2007 in the Marimbondo-Fumas Hydroelectric Plant reservoir, Rio Grande, municipality of Icém in northwestern São Paulo state. The individuals were sexed, carapace widths were measured, and the gonads were examined macroscopically. In total, 1002 individuals were analyzed, consisting of 568 males and 434 females, of which 4 were ovigerous and 35 carried early juveniles in the incubatory chamber. The largest numbers of reproductive individuals of both sexes were recorded during the winter and spring months before spawning, which occurred in the spring. Intense juvenile recruitment and the highest rainfall levels were observed during the Southern Hemisphere summer. The results indicate that spawning can be considered seasonal, and the simultaneous emergence of juveniles with high rainfall levels is probably the result of the higher availability of food and potential sites for protection against predators. The skewed sex ratio (♂ 1:0.76 ♀) may be associated with growth rates, mortality, food restriction, behavioral differences, migration, and differential habitat use between the sexes. The similar maximum size (CW∞) and growth constant (k) for males (k = 1.78 y-1, CW = 61.43 mm) and females (k = 1.67 y-1, CW = 60.66 mm) may be associated with different energy investment strategies between the sexes. Additionally, a closed season is proposed for the species. © The Crustacean Society, 2013. Published by Brill NV, Leiden.
Keywords: Growth; Juvenile recruitment; Reproduction; Trichodactylidae